2022
DOI: 10.20473/jphrecode.v5i2.27923
|View full text |Cite
|
Sign up to set email alerts
|

The Risk Factors of Hypertension in Indonesia (Data Study of Indonesian Family Life Survey 5)

Abstract: Background: Hypertension is a worrying disease, as it often does not cause symptoms. According to WHO, this disease affects 22% of the world's population, while hypertension has affected 25% of the population in Southeast Asia. In Indonesia, the prevalence of hypertensive disease increases from year to year. The suspected risk factors for hypertension are gender, age, genetics, smoking obesity, physical activity, and stress. Purpose: analyze factors that affect the prevalence of hypertension in Indonesia based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Hypertension is also one of the most significant comorbidities that aggravate several diseases, such as stroke, myocardial infarction, heart failure, and kidney failure (Iqbal & Jamal, 2022). In a study mentioned several risk factors that can cause hypertension in Indonesia, including gender, age, physical activity, and obesity (Khasanah, 2022). In this study, hypertension was found to be more common in the group >45 years of age.…”
Section: Health Screeningmentioning
confidence: 48%
“…Hypertension is also one of the most significant comorbidities that aggravate several diseases, such as stroke, myocardial infarction, heart failure, and kidney failure (Iqbal & Jamal, 2022). In a study mentioned several risk factors that can cause hypertension in Indonesia, including gender, age, physical activity, and obesity (Khasanah, 2022). In this study, hypertension was found to be more common in the group >45 years of age.…”
Section: Health Screeningmentioning
confidence: 48%
“…The World Health Organization's most current data indicates that one in three adults worldwide suffers from hypertension [32]. Hypertension was the third Original Article leading cause of mortality in Indonesia [33]. The prevalence of hypertension in adults over 18 years in the country was 25.8% in 2013 [24].…”
Section: Discussionmentioning
confidence: 99%
“…Berbeda dengan pasien lakilaki pasien wanita mengalami peningkatan risiko hipertensi pada masa menopause. Saat menopause, tingkat hormon estrogen menurun, yang dapat menyebabkan pasien wanita rentan mengalami hipertensi (Defianna et al, 2021;Khasanah, 2022). Selain itu, bertambahnya usia seseorang berkaitan dengan resiko terjadinya hipertensi.…”
Section: Metodeunclassified